Effectiveness of the program “La Era lives happily without EDAS” knowledge, attitudes and practices of the management of acute diarrhea by mothers of children under age 4 in the Town Center Virgen del Carmen - La Era March to December 2013 - Rodríguez Villanueva, Marisol (2019)
Objective: To determine the effectiveness of the program “La Era lives happily without EDAS” in knowledge,attitudes and practices on the management of acute diarrheal diseases (EDAS) of mothers of children underfour years of the Town Centre Virgen del Carmen La Era. Material and Methods: The study was quantitativeprobabilistic no pre experimental design because we worked with one group to which was applied a pre testand post test to determine program effectiveness. Results: After implementation of the program most excellentknowledge level evidence on the management of EDAS (93.3%) and only 6.7% have a regular knowledge;moreover, most have a highly favorable (86.7%) compared to management of EDAS attitude. The same appliesto practices where mothers program then practiced mostly items that prevent the occurrence of acute diarrhealdiseases. Conclusions: the “La Era lives happily without EDAS” was effective in increasing the level ofknowledge, attitudes and practices on prevention of acute diarrheal disease in mothers of children under fouryears of the Town Centre Virgen del Carmen La Era.